2014
DOI: 10.1371/journal.pone.0108922
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the Six-Minute Walk Distance in Children with Sickle Cell Disease Is Correlated with Silent Infarct: Results from a Cross-Sectional Evaluation in a Single Center in Belgium

Abstract: BackgroundThe 6-minute walk test (6MWT) is used in adults and children affected by a wide range of chronic diseases to evaluate their sub-maximal exercise capacity. It reflects the global response of various physiological systems in a situation simulating a daily life activity.MethodsWe analyzed factors affecting the 6MWT in 46 Sickle Cell Disease children. Forty-two were treated with hydroxyurea (HU). Patients with normal test (>80% of the age-standardized predicted value) were compared to patients with abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
2
9
0
2
Order By: Relevance
“…Two tests were performed within 30 minutes, and when there were conflicting results between the tests, a third test was performed. A normal result was defined as a 6MWD > 80% of predicted for age, a moderate result was defined as a 6MWD between 60% and 80% of predicted, and a severe result was defined as a 6MWD < 60% of predicted 29 . A significant decrease in SpO 2 (desaturation) was defined as that ≥ 3% relative to baseline 30 …”
Section: Methodsmentioning
confidence: 99%
“…Two tests were performed within 30 minutes, and when there were conflicting results between the tests, a third test was performed. A normal result was defined as a 6MWD > 80% of predicted for age, a moderate result was defined as a 6MWD between 60% and 80% of predicted, and a severe result was defined as a 6MWD < 60% of predicted 29 . A significant decrease in SpO 2 (desaturation) was defined as that ≥ 3% relative to baseline 30 …”
Section: Methodsmentioning
confidence: 99%
“…Then the distance walked was noted and the percentage of predicted distance was calculated by Geigers' standardized formula [31] according to age, sex and height, as previously done [32]. The 6MWT was considered as normal if the performance was more than 80% of the age-standardised predicted value and abnormal otherwise [33].…”
Section: Six-minute Walk Test (6mwt)mentioning
confidence: 99%
“…In addition, the 6MWT performance inversely correlates with the severity of the disease. [12] For instance, a recent study reported an independent association between the 6MWT performance and the presence of silent infarcts in children with SCA and no severe cardiopulmonary dysfunction [13]. Anthi et al [12] previously showed the usefulness of using the 6MWT distance as an index of pulmonary hypertension and cardiopulmonary function in adults with SCA.…”
Section: Introductionmentioning
confidence: 99%